2005
DOI: 10.1212/01.wnl.0000178896.44905.33
|View full text |Cite
|
Sign up to set email alerts
|

ERG and anatomical abnormalities suggesting retinopathy in dementia with Lewy bodies

Abstract: The authors used flash electroretinography to demonstrate dysfunction of the photopic and scotopic retina in patients with dementia with Lewy bodies and visual hallucinations (VHs) compared with patients with Parkinson disease, patients without VHs, and controls. The retinal dysfunction may be related to slight alteration of the photoreceptors and numerous pale inclusions in the outer plexiform layer found at the post mortem examination, suggesting a specific retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 8 publications
2
33
1
Order By: Relevance
“…119 Changes also in DLB 120 ERG Controversial in AD. [123][124][125][126][127][128]210 Defects likely in DLB 129 …”
Section: Visual Dysfunction In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…119 Changes also in DLB 120 ERG Controversial in AD. [123][124][125][126][127][128]210 Defects likely in DLB 129 …”
Section: Visual Dysfunction In Dementiamentioning
confidence: 99%
“…128 The fERG has also been used to demonstrate dysfunction of the scotopic and photopic systems of the retina in DLB subjects. 129 The deficits were attributed to pathological alterations in the photoreceptors which were accompanied by 'pale inclusions' in the outer plexiform layer, particularly in the peripheral retina. Immunohistochemistry and structural analyses indicated that these inclusions differed from LB.…”
Section: Electroretinogrammentioning
confidence: 99%
“…One such postmortem study has suggested swelling of photoreceptors and loss of RGCs as well as pale intracellular inclusions in the outer plexiform layer of the retina in postmortem patients with dementia with Lewy bodies. 6 Other human and animal studies also have shown that there is a decrease in the level of dopamine in amacrine, horizontal, and interplexiform cells of the retina, and that dopamine-containing layers of the retina become thinner. [7][8] The ganglion cell damage or alterations in retinal dopamine-containing cells has also been shown with 2 electroretinograpy studies.…”
mentioning
confidence: 97%
“…7 As the authors also note, the possible retinal involvement to explain color vision abnormalities and possible peripheral autonomic ganglia involvement to explain autonomic dysfunction does not fit into the current Braak schema. Yet other investigators have shown Lewy body pathology in the retina, 8 and peripheral autonomic ganglia, 9 suggesting LBD is more widespread than currently conceived in the Braak staging system.…”
mentioning
confidence: 99%